Recipients of the DLSU mini-grants for creative writing AY 2021-2022 - Bienvenido N. Santos Creative Writing Center-De La Salle University, Manila (Animo Repository, 2021)
The College of Liberal Arts Office of Research & Advanced Studies in cooperation with Office of the Vice President for Research & Innovation and Bienvenido N. Santos Creative Writing Center announced the recipients of the DLSU Mini-Grants for Creative Writing 2021-2022.